Gain of chromosome arm 1q in atypical meningioma correlates with shorter progression-free survival - Jansen, M. (2012)
AIMS: Atypical (WHO grade II) meningiomas have moderately high recurrence rates; even for completely resected tumours, approximately one-third will recur. Postoperative radiotherapy (RT) may aid local control and improve survival, but carries the risk of side effects. More accurate prediction of recurrence risk is therefore needed for patients with atypical meningioma. Previously, we used high-resolution array CGH to identify genetic variations in 47 primary atypical meningiomas and found that approximately 60% of tumors show gain of 1q at 1q25.1 and 1q25.3 to 1q32.1 and that 1q gain appeared to correlate with shorter progression-free survival. This study aimed to validate and extend these findings in an independent sample. METHODS: 86 completely resected atypical meningiomas (with 25 recurrences) from two neurosurgical centres in Ireland were identified and clinical follow up was obtained. Utilizing a dual-colour interphase FISH assay, 1q gain was assessed using BAC probes directed against 1q25.1 and 1q32.1. RESULTS: The results confirm the high prevalence of 1q gain at these loci in atypical meningiomas. We further show that gain at 1q32.1 and age each correlate with progression-free survival in patients who have undergone complete surgical resection of atypical meningiomas. CONCLUSIONS: These independent findings suggest that assessment of 1q copy number status can add clinically useful information for the management of patients with atypical meningiomas.